Siwalik Flora from Koilabas Area in the Nepal Himalaya and its Significance on Palaeoenvironment and Phytogeography - Prasad, Mahesh (Journal of Nepal Geological Society, 1995)
The plant fossil assemblages recovered from the Siwalik sediments of Koilabas area (Darwaja and Chorkholi) in the Western part of Nepal are described. An attempt has been made to deduce the palaeoclimate and phytogeography of the area during sedimentation. Based on available data, Low land mixed mesophytic forest communities of broad leaved semievergreen to evergreen trees appeared to be nourishing around Koilabas area during Siwalik period. Analysis of the present distribution of the modem equivalents of the fossils shows that about 80 percent of taxa have disappeared from the area and have got migrated to other suitable regions like northeast India, Bangladesh, Myanmar and Malaya where they have found favourable condition for their longer survival. It indicates a positive change in the climate after Mio-Pliocene times. The study of physiognomic characters of the fossil leaves in relation to climate has been done and based on these characters a well as habit and habitat of comparable taxa, a tropical (warm humid) climate with plenty of rainfall has been deduced.